Numerical Study of Scale Effects of Tip Clearance Flow Field of Pump-Jet Propulsor - YANG Chun, GUO Chunyu, SUN Cong, WANG Chao, YUE Qihui (Shanghai Jiaotong Daxue xuebao)
Due to the tip clearance of the pump-jet propulsor (PJP), the flow field characteristics in the PJP are more complicated. To explore the influence of scale effects on the tip clearance flow field of PJP, the unsteady Reynolds-averaged Navier-Stokes (URANS) equation and the SST k-ω turbulence model are used. The computational domain is discretized by structured grid, and the sliding grid is used to deal with the relative motion between the rotor and stationary components. The feasibility of the numerical method is verified by grid uncertainty analysis, and the numerical results are in good agreement with the model-scale PJP experimental data. The open water performance of the three scale PJP models is numerically calculated and analyzed from the perspective of vorticity field and pressure field. The results show that the efficiency of the full-scale PJP model will be improved under all the advance coefficients, the vorticity collapse of the full-scale PJP is earlier, the intensity is lower, the pressure coefficient of the TLV vortex core center is smaller, and the fluctuating pressure amplitude between the tip clearance is lower.